2022
DOI: 10.3390/cancers14246087
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Bevacizumab on Visual Function, Tumor Size, and Toxicity in Pediatric Progressive Optic Pathway Glioma: A Retrospective Nationwide Multicentre Study

Abstract: Backgrounds: Bevacizumab (BVZ) is used as a subsequent line of treatment for pediatric optic pathway glioma (OPG) in the case of progression. Data on the treatment effect concerning tumor progression and visual function are scarce and nationwide studies are lacking. Methods: We performed a retrospective, nationwide, multicentre cohort study including all pediatric patients with OPG treated with BVZ in the Netherlands (2009–2021). Progression-free survival, change in visual acuity and visual field, MRI-based ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…[20] Also, targeted treatment with bevacizumab led to treatment response after progression in some studies. [21] In our study two patients who were being evaluated for malnutrition, were diagnosed with OPG in MRI. Diencephalic syndrome was observed in these two patients.…”
Section: Discussionmentioning
confidence: 96%
“…[20] Also, targeted treatment with bevacizumab led to treatment response after progression in some studies. [21] In our study two patients who were being evaluated for malnutrition, were diagnosed with OPG in MRI. Diencephalic syndrome was observed in these two patients.…”
Section: Discussionmentioning
confidence: 96%
“…Case studies have shown that static, spatially and temporally correlated audiovisual stimuli displayed on computer screens can also improve perception in the blind field in adults/older adults with hemianopia after stroke, but require frequent clinic visits 49,50 . In addition, recent retrospective studies reported variable benefits of active Bevacizumab treatment on visual acuity and visual field in children with optic pathway glioma, although these improvements were often lost after discontinuation of the treatment [9][10][11][12] . The mechanisms underlying these temporary improvements are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Sparse evidence shows that visual acuity and visual field deficits can be improved with Bevacizumab, an inhibitor of vascular endothelial growth factor, in children with optic nerve gliomas. However, the benefits are not sustained after discontinuation of the drug and there is potential toxicity [9][10][11][12] . In our previous case series 13,14 , we used immersive virtual-reality (IVR) in the Oculus Go headset to deliver a personalized, remotely controlled, dynamic audiovisual stimulation in young adult patients with stable hemianopia (> 18 months) consecutive to a paediatric brain tumour.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Средняя продолжительность использования бевацизумаба составила 169 дней [4]. В ряде публикаций продемонстрирована эффективность и безопасность указанного агента при рецидивирующей медуллобластоме и глиоме у детей [6][7][8][9][10][11], что, вероятно, объясняет высокую распространенность его приме-…”
Section: безопасность противоопухолевой лекарственной терапии «вне ин...unclassified